PENGARUH BAURAN PEMASARAN JASA TERHADAP NILAI JASA WISATA ALAM DI KABUPATEN BOJONEGORO - Susilowati Rahayu; Ekky Widyasari; Ahmad Nafis; Siti Tri Arniati; Rizna Ayu Wijayanti (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2016)
This study aims to examines the effect of implementation of service marketing mix on the process of tourist decision making to make a tour in Bojonegoro residence. There are Negeri Atas Angin, Air Terjun Krondonan, Telaga grogolan, and Kedung Maor that booming torism destination. This study mainly used the service marketing approach. The sampling method used was purposive sampling technique. The analyze shows that mixed marketing performance gave a significant influence to the tourism service value. A deeper analysis revealed that among the aspects, mixed marketing performance which was consisted of product, price, place, promotion, people, physical evidence, and process needs to improve by the operator of natural tourism.